Pathological Characteristics of Primary Bladder Carcinoma Treated at a Tertiary Care Hospital and Changing Demographics of Bladder Cancer in Sri Lanka. (14th January 2016) - Sasikumar, S.; Wijayarathna, K. S. N.; Karunaratne, K. A. M. S.; Gobi, U.; Pathmeswaran, A.; Abeygunasekera, Anuruddha M.
Abstract : Objectives . The aim was to compare demographics and pathological features of bladder carcinoma treated in a urology unit with findings of previous studies done in Sri Lanka. Materials and Methods . Data of newly diagnosed patients with bladder cancer in a tertiary referral centre from 2011 to 2014 were analysed. Data on bladder cancers diagnosed from 1993 to 2014 were obtained from previous publications and Sri Lanka Cancer Registry. Results . There were 148 patients and mean age was 65 years. Male to female ratio was 4.1 : 1. Urothelial carcinoma (UC) was found in 89.2% of patients. Muscle invasion was noted in 35% of patients compared to 48.4% two decades ago. In patients with UC, 16.5% were found to have pT1 high grade tumour. It was 5.3% from 1993 to 2000. Pure squamous cell carcinoma was found in 8.1% of patients while primary or de novo carcinoma in situ (not associated with high grade pT1 tumours) was seen in one patient only. Conclusions . The percentage of squamous carcinoma is higher among Sri Lankan patients while primary carcinoma in situ is a rarity. The percentage of muscle invasive disease has decreased while the percentage of pT1 high grade tumours has increased during the last two decades in Sri Lanka.